1990
DOI: 10.1002/jez.1402540203
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐adaptive differences between the M4 lactate dehydrogenases of stenothermal and eurythermal sciaenid fishes

Abstract: The effects of temperature on the apparent Michaelis-Menten constant (K,) of pyruvate were determined for M,-lactate dehydrogenases (LDHs) of 15 species of the teleost family Sciaenidae from habitats differing in average temperature and temperature range. The central question addressed was whether adaptive differences in the effect of temperature on an important kinetic parameter, K,, reflect selection based on the range of temperatures experienced by the species, the highest temperature encountered by the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…We found that species differences in the relationship of K m Versus temperature for LDH-As favor conservation of K m for substrate and cofactor at physiological temperatures. These results agree with previous findings for dehydrogenase enzymes of other vertebrates and invertebrates (Graves & Somero, 1982;Coppes & Somero, 1990;Dahlhoff & Somero, 1993), and show that even relatively minor changes in temperature, such as those predicted by some models of global warming, appear adequate to favor selection for adaptive change in proteins.…”
Section: Discussionsupporting
confidence: 92%
“…We found that species differences in the relationship of K m Versus temperature for LDH-As favor conservation of K m for substrate and cofactor at physiological temperatures. These results agree with previous findings for dehydrogenase enzymes of other vertebrates and invertebrates (Graves & Somero, 1982;Coppes & Somero, 1990;Dahlhoff & Somero, 1993), and show that even relatively minor changes in temperature, such as those predicted by some models of global warming, appear adequate to favor selection for adaptive change in proteins.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, B-isoforms are characteristically more susceptible to substrate inhibition, channeling more pyruvate into the Kreb's cycle and functioning mainly as lactate oxidases. The apparent K m (pyr) values obtained here have been compared with other fish LDH K m values (Wuntch and Goldberg, 1970;Panepucci et al, 1987;Coppes and Somero, 1990;Almeida-Val et al, 1991). All were found to be similar to K m values obtained for muscle and heart LDH or their purified isoforms.…”
Section: Discussionsupporting
confidence: 73%
“…Some components present in the fertilizer industrial effluent interact together and produce toxicity to aquatic organisms for example the interaction between dissolve oxygen and elevated ammonia has been shown to alter the respiratory physiology of fresh water fish (Pickering and Pottinger 1987). These findings indicated that the inhibitory effect of industrial effluent on the activity of LDH may be mediated via formation of enzyme-inhibitor complex leading to impairment of carbohydrate metabolism (Panepucci et al 1984(Panepucci et al , 1987Copper and Somero 1990;Sharma and Gopal 1995).…”
Section: Resultsmentioning
confidence: 99%